Nutrient composition of Algerian strawberry-tree fruits (Arbutus unedo L.) - Boussalah, N. (2018)
Arbutus unedo L. (strawberry-tree fruit) is indigenous plant in North Africa with few published works about the composition of its fruits. For their valorization, morphological and chemical characterizations were carried out for two harvesting seasons of four different areas of Algeria. Materials and methods. Wild strawberry-tree fruits were collected in four different sites located in Tell Atlas, and two different seasons. Fruit size and shape, pH, titratable acidity, moisture, total available carbohydrate (TAC), soluble sugars, dietary fiber, protein, lipid, ash, fatty acids and mineral composition (K, Na, Ca, Mg, Fe, Cu, Mn, Zn, Ni and Cd) were determined. Results and discussion. Fruit contents (in g kg−1) varied between 637.3 ± 33.8 to 741.3 ±12.0, 126.8 ± 11.1 to 189.3 ± 4.1, 22.6 ± 2.2 to 35.5 ± 2.1, 5.1 ± 0.3 to 8.8 ± 0.5 for moisture, TAC, protein and lipid, respectively. For iron, fruit weight and polyunsaturated fatty acids (PUFA), the contents varied between 7.01 ± 0.15 to 17.24 ± 0.74 mg kg−1 of fruit, 4.91 ± 1.58 to 6.76 ± 2.04 g and 56.34 ± 1.37 to 68.18 ± 0.14% of lipid, respectively. Conclusion. This study provides original data about the morphological and chemical composition of strawberry-tree fruits from Algeria. The results show that the fruits can be essentially a potential source of dietary fiber, PUFA and iron.